2020
DOI: 10.1161/strokeaha.119.027664
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Risk of Small Unruptured Intracranial Aneurysms in Japanese Adults

Abstract: Background and Purpose— Therapeutic decision making for small unruptured intracranial aneurysms (<10 mm) is difficult. We aimed to develop a rupture risk model for small intracranial aneurysms in Japanese adults, including clinical, morphological, and hemodynamic parameters. Methods— We analyzed 338 small unruptured aneurysms; 35 ruptured during the observation period, and 303 remained stable. Clinical, morphological, and hemodynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
5
33
0
Order By: Relevance
“…Although incidental small paraclinoid UIAs (≤5 mm) have a relatively lower rupture and growth risk, Jeon et al (25) indicated that arterial branch-related location was a significant predictive factor for UIA progression. Recently, Suzuki et al showed that UIA (<10 mm) located at a bifurcation was a risk factor for rupture (26). These reports are also consistent with our study in that UIA located at a bifurcation was a risk factor for progression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although incidental small paraclinoid UIAs (≤5 mm) have a relatively lower rupture and growth risk, Jeon et al (25) indicated that arterial branch-related location was a significant predictive factor for UIA progression. Recently, Suzuki et al showed that UIA (<10 mm) located at a bifurcation was a risk factor for rupture (26). These reports are also consistent with our study in that UIA located at a bifurcation was a risk factor for progression.…”
Section: Discussionsupporting
confidence: 93%
“…Conflicts of Interest: All authors have completed the ICMJE uniform disclosure form (available at http://dx.doi. org/10.21037/qims- [21][22][23][24][25][26][27][28][29][30][31][32]. The authors have no conflicts of interest to declare.…”
Section: Footnotementioning
confidence: 99%
“…Current scoring systems are not robust, especially for small aneurysms, which have to be modelled specifically due to their unique histologic characteristics. [10][11][12] Therefore, novel methodologies are required to construct rupture-risk models for small aneurysms to facilitate clinical decisions. 13,14 Aneurysms were often treated only if any change in size or morphology of the aneurysm was detected during follow-up, which would result in a serious bias in the longitudinal study.…”
mentioning
confidence: 99%
“…Other possible causes include differences in basic patient characteristics related to risk factors for IA. 26) The proportion of patients with multiple IAs was 47.4% in the present trial and 33.2% in the SUAVe study while hypertensive patients comprised 40% and 24.9%, respectively.…”
Section: Discussionmentioning
confidence: 44%